On Special Weakly Riccisymmetric and Generalized Ricci-Recurrent Trans-Sasakian Structures: Sudhakar Kumar Chaubey - Team, Support (Thai Journal of Mathematics, 2018)
The present paper deals with the trans-Sasakian structure admitting an m−projective curvature tensor. In the last, the properties of special weakly Riccisymmetric and generalized Ricci-recurrent trans-Sasakian structures are studied.